2015
DOI: 10.1007/s00253-015-7188-7
|View full text |Cite
|
Sign up to set email alerts
|

Seed-borne nature of a begomovirus, Mung bean yellow mosaic virus in black gram

Abstract: The yellow mosaic viruses (YMV) infecting legumes are considered to be the most devastating begomoviruses as they incite considerable yield loss. The yellow discoloration of pods and seeds of infected plants and symptom emergence in the very first trifoliate leaf of the plants in the field were suggestive that the virus may be seed borne, which was investigated in the present study. The distribution of the virus in various parts of the seeds of black gram (Vigna mungo L. Hepper) plants naturally infected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 19 publications
1
41
2
3
Order By: Relevance
“…Similar conclusions can be drawn from our results. However, given that the seeds of mung beans are large enough, confirmation of the presence of the MBYMV virion particles in a single mung bean seed was possible by performing DAS-ELISA and ISEM experiments [18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions can be drawn from our results. However, given that the seeds of mung beans are large enough, confirmation of the presence of the MBYMV virion particles in a single mung bean seed was possible by performing DAS-ELISA and ISEM experiments [18]. …”
Section: Discussionmentioning
confidence: 99%
“…However, maize streak virus (genus Mastrevirus ) has been experimentally transmitted in maize through vascular puncture of the seeds [15]. More recently, Kim et al [16], Kil et al [17], and Kothandaraman et al [18] reported seed transmission of sweet potato leaf curl virus (SPLCV), tomato yellow leaf curl virus (TYLCV), and mung bean yellow mosaic virus (MBYMV), three distinct begomoviruses in sweet potato ( Ipomoea batatas ), tomato ( Solanum lycopersicum ), and black gram ( Vigna mungo ), respectively. In the present paper, we provide evidence for natural and experimental seed transmission of BCTV-Svr, a curtovirus, and BCTIV, a becurtovirus, in a local cultivar of petunia.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of DAS-ELISA, they reported the seed-borne nature of DoYMV. Similarly, DAS-ELISA and immunosorbent electron microscopy have been performed to detect the presence of virus particles by Kothandaraman et al [125] in black gram. AV 494/AC 1048 FJ821189 GCC(C/T)AT(G/A)TA(T/C)AG (A/G)AAGCC(A/C)AG…”
Section: Effective Phenotyping Proceduresmentioning
confidence: 99%
“…However, it was recently confirmed that TYLCV-infected tomato seeds could transmit infectious virus ( Kil et al, 2016 ). In addition, seed transmission of other begomoviruses such as Sweet potato leaf curl virus (SPLCV) and Mung bean yellow mosaic virus (MYMV) was also reported in sweet potato and black gram ( Kim et al, 2015 ; Kothandaraman et al, 2016 ). Seed transmission of TYLCV has also been verified in sweet pepper (unpublished data).…”
mentioning
confidence: 99%